Leaf Removal at Véraison and Foliar K+ Application to Beibinghong Vines Improved Berry Quality under Cold-Climate Conditions - Zhao Le; Wei Zheng; Mengde Dong; Ming Cai; Gastón Gutiérrez-Gamboa; Baoshan Sun (Plants, 2022)
(1) Background: Beibinghong is a grapevine variety that is well distributed in Northeastern China due to its adaptation to extreme cold conditions and vine diseases. Nonetheless, Beibinghong wines are extremely acidic and rich in phenolic compounds. The aim of this research was to study the effects of leaf removal at véraison and foliar K+ applications on Beibinghong vines to reduce the acidity and increase their polyphenol content. (2) Methods: Beibinghong berries were harvested when they reached close to 20 °Brix, and the physicochemical parameters were determined. (3) Results: Leaf removal at véraison plus K+ foliar applications to Beibinghong vines decreased the titratable acidity and increased the total phenolic and phenolic acid contents compared with the control. Moreover, the titratable acidity in the Beibinghong berries was negatively related to their total contents of phenols, proanthocyanidins, and anthocyanins. (4) Conclusions: Leaf removal at véraison performed with foliar K+ applications to vines could be an interesting alternative for Beibinghong production under cold-climate viticulture because it allows for a decrease in the acidity and an increase in the phenolic content of the berries, without incurring the risk of sunburn.